1903
DOI: 10.1086/621112
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity of the Glacial Period on Long Island

Abstract: Gardiners Island, situated between the two eastern flukes of Long Island, presents many of the features shown on Nantucket, Marthas Vineyard, and Block Island. The succession is essentially the same and the correlation evident. It therefore forms a ready point of reference between Long Island, on the one hand, and the New England islands, on the other. The structure of the island can best be worked out on the northeast shore, where the bluffs are quite high and are kept clean by the constant encroachment of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1906
1906
1992
1992

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…De Varona (1896), Crosby (1900), and Freeman (1900) studied the water resources of the western part of Long Island. Veatch (1903) described the glacial geology and named the Pleistocene Jameco Gravel. Fuller (1905c) described the geology of Fisher's Island and named the Pliocene (?)…”
Section: G8mentioning
confidence: 99%
“…De Varona (1896), Crosby (1900), and Freeman (1900) studied the water resources of the western part of Long Island. Veatch (1903) described the glacial geology and named the Pleistocene Jameco Gravel. Fuller (1905c) described the geology of Fisher's Island and named the Pliocene (?)…”
Section: G8mentioning
confidence: 99%
“…The belt is nearly 19 miles long; and at Watch Hill, in the southwestern tip of Rhode Island, it extends into Block Island Sound. Upham (1879) suggested that this moraine is a continuation of the chain of morainic hills along the north shore of Long Island to which Veatch (1903) later gave the name Harbor Hill moraine. The Buzzards Bay moraine of southern Massachusetts (Woodworth and Wigglesworth, 1934) has been generally considered its continuation to the east ( fig.…”
Section: Descriptionmentioning
confidence: 99%